Exploring the effects of resveratrol and β-hydroxy-β-methylbutyric acid under different protein levels on the ileal health of tibetan sheep - Gao, Wei; Zhu, Kaina; Zhang, Xianhua; Saren, Geerli; Zhang, Yu; Gan, Jiacheng; Hou, Shengzhen; Gui, Linsheng (Frontiers in Microbiology, 2025)
IntroductionResveratrol (RES) and β-hydroxy-β-methylbutyric acid (HMB) have been shown to improve growth performance in Tibetan sheep by regulating the gut microbiota. This study explored the effects of RES and HMB supplementation on the microbial composition and metabolite levels in the ileum of Tibetan sheep receiving diets with different protein levels.MethodsIn a 2 × 2 factorial arrangement, consisting of dietary protein levels (12% and 14%) and feed additive levels (no addition; and RES 1.50 g/d and HMB 1.25 g/d addition). A total of 120 healthy two-month-old male Tibetan lambs (16.87 ± 0.31) were randomly divided into 4 groups (n = 6): 12% protein level group (L), the 12% protein level supplemented with RES and HMB group (L-RES-HMB); the 14% protein level group (H); and the 14% protein level supplemented with RES and HMB group (H-RES-HMB).ResultsThe results demonstrated that the activities of digestive enzymes (β-amylase, trypsin, lipase, and cellulase), the levels of antibodies (IgA and IgM), and the contents of short-chain fatty acid (SCFA) (butyric acid) were significantly increased in the H-RES-HMB group (P < 0.05). Additionally, RES and HMB supplementation affected the morphology of ileum tissue, improving the villus height, crypt depth, and mucosal thickness (P < 0.05). Microbial analysis revealed that compared with the L-RES-HMB group, the H-RES-HMB group had a higher abundance of Planctomycetota, Solibacillus, and Paenibacillus (P < 0.05). Metabolomics analysis revealed a total of 229 significantly different metabolites, of which Irinotecan, Erdosteine thioacid, 4,4’-diaminodiphenylmethane, and Morphine N-oxide emerged as the key up-regulated metabolites. These differential metabolites were mainly enriched in pathways such as protein digestion and absorption, metabolic pathways, and mineral absorption.DiscussionOverall, when the dietary protein content was 14%, digestive enzyme activities, immune responses, and SCFAs levels in the ileum were improved, and the mucosal morphology of the ileum was enhanced. When the 14% protein diet was supplemented with RES and HMB, the concentration of butyric acid was increased. This increase was due to the regulation of the ileum microbiota (Firmicutes and Clostridium_sensu_stricto_1) and metabolites (xanthine and uric acid), which promoted the activities of digestive enzymes and immune responses and improved mucosal morphology in the ileum.